Brief Research Report: Pilot testing an identity-based relevance-writing intervention to support developmental community college students' persistence. Issue 1 (2nd January 2022) - Perez, Tony; Gregory, Kristen H.; Baker, Peter B.
Abstract: We pilot tested an identity-based relevance-writing intervention designed to support developmental community college students' ( N  = 54) educational commitment, value, and persistence. The intervention was embedded within regular journal assignments in two study skills courses with a third section serving as a comparison group. The intervention prompted students to explore how course topics connected to their identity. Results indicated large differences between groups in identity connections made in assignments and follow-up educational commitment and moderate differences in follow-up task value, all favoring the intervention group. There were no differences between groups in course enrollment eight months later. This pilot study offers promising preliminary evidence that an identity-based relevance-writing intervention may be effective in supporting developmental community college students' academic persistence.